Substance abuse prevention among secondary school students in Malaysia / Chan Yuen Fook ... [et al.] - Chan, Yuen Fook; Kaur Sidhu, Gurnam; Mohd. Hussin, Abdul Halim; Wee, Eng Hoe; Lim, Peck Choo; Abd. Hamid, Mohd. Zaiham (Research Management Institute (RMI), 2012)
Substance abuse is an act of misuse or excessive use of alcohol, tobacco and illicit drugs which has become one of the world’s leading problems today. The number of adolescents involved in illegal substances and illicit drugs in Malaysia has increased over the years. Statistics reveal that almost 80% of the students claim that they began smoking while still in school. Since the figure is alarming, it is important to investigate this matter. Therefore, the objectives of this study are to identify problems of substance abuse among secondary school students and also investigate the effectiveness of prevention measures that have been implemented in secondary schools. A mixed-method approach was chosen to triangulate the data obtained in this study. Five different instruments namely teacher questionnaire, student questionnaire, checklist, interview questions, and quiz were used to collect both the quantitative and qualitative data. A total of 18 high risk secondary schools were selected from Selangor, WPKL, Penang, Negeri Sembilan and Melaka. Finally, a total of 270 teachers and 1800 students from the 18 high risk schools were selected from these states.